Biology and Health Education Curriculum on Liver Fluke Disease and Cholangiocarcinoma Prevention among Primary School Students in Endemic Areas to Support Sustainable Development Goals (SDGs): Bibliometric and Mixed-Methods Needs Analysis - Sampan Thinwiangthong; Ladda Silanoi; Piyawan Srisuruk; Angkana Tungkasamit; Somkamon Boonmee; Suchat Thangsathirasima; Pilunthana Supadol; Porramate Jaratmetakul (Bumi Publikasi Nusantara, 2027)
Liver fluke disease and cholangiocarcinoma remain major health problems in endemic areas of northeastern Thailand. This study examined essential needs for developing a biology and health education curriculum to prevent these diseases among primary school students and to support SDGs-oriented health literacy. A bibliometric and mixed-methods needs analysis was conducted with 455 participants, including school administrators, teachers, and students. Quantitative data were analyzed using descriptive statistics and priority needs analysis, while qualitative data were analyzed through content analysis. The findings showed high needs for developmentally appropriate curriculum, creative media, technology-supported learning, flexible implementation, and systematic assessment. The study provides evidence for school-based curriculum development to strengthen disease prevention awareness and community health.